Answer:
f(x)=6x+15
Step-by-step explanation:
first you find the gradient of the equation with the gradient formula by using the two given points
the gradient is 6, so using the slope equation which is y=mx+b sub 6 into the gradient
you then get y=6x+b
to find b just sub in any of the points and solve the equation.
ps. f(x) essentially stands for a y so don't get confused
hope this helps :)
Answer:
y = 6x + 15.
Step-by-step explanation:
The slope of the line joining these 2 points =
(9-3)/(-1-(-2))
= 6/1
= 6
Use the point-slope form of a straight line:
y - y1 =m(x - x1) Here m = 6 and (x1, y1) will be (-2, 3), so:
y - 3 = 6(x -(-2))
y - 3 = 6(x + 2)
y = 6x + 12 + 3
y = 6x + 15.
b. (-3,6)
c. (3,2)
d. (3,5)
2. Which equation is the equation of a line that passes through (-10,3) and is perpendicular to y=5x-7?
a. y = 5x + 53
b. y = -1/5x - 7
c. y = -1/5x + 1
d. y = 1/5x + 5
-3x2+243=0